Morvan syndrome: clinical and serological observations in 29 cases. - Irani, SR; Pettingill, P; Kleopa, K; Schiza, N; Waters, P; Mazia, C; Zuliani, L; Watanabe, O; Lang, B; Buckley, C; Vincent, A (2012)
OBJECTIVE: A study was undertaken to describe the clinical spectrum, voltage-gated potassium channel (VGKC) complex antibody specificities, and central nervous system localization of antibody binding in 29 patients diagnosed with Morvan syndrome (MoS). METHODS: Clinical data were collected using questionnaires. Radioimmunoassay, cell-based assays, and mouse brain immunohistochemistry were used to characterize the serum antibodies. RESULTS: Neuromyotonia (100%), neuropsychiatric features (insomnia 89.7%, confusion 65.5%, amnesia 55.6%, hallucinations 51.9%), dysautonomia (hyperhidrosis 86.2%, cardiovascular 48.3%), and neuropathic pain (62.1%) were the most common manifestations. A total of 93.1% of MoS patients were male. VGKC-complex antibodies were present in 23 of 29 (79%) MoS patients at referral; 24 of 27 available sera had CASPR2, LGI1, or both CASPR2 and LGI1 antibodies (3 also with contactin-2 antibodies). CASPR2 antibodies were generally higher titer than LGI1 antibodies. Tumors (41.4%), mainly thymomas, were associated with CASPR2 antibodies and a poor prognosis, whereas LGI1 antibodies were associated with serum hyponatremia. In brain tissue regions including the hypothalamus, raphe, and locus coeruleus, commercial antibodies to LGI1 bound to neuronal cell bodies including the antidiuretic hormone-secreting and orexin-secreting hypothalamic neurons, whereas CASPR2 commercial antibodies bound more often to the neuropil. MoS antibodies bound similarly, but there was evidence of additional antibodies in some sera that were not adsorbed by LGI1- or CASPR2-expressing cells and bound to mouse Caspr2(-/-) tissue. INTERPRETATION: MoS is clinically distinct from other VGKC-complex antibody-associated conditions, and usually is associated with high-titer CASPR2 antibodies, often accompanied by lower-titer LGI1 antibodies. CASPR2 and LGI1 antibodies bind to multiple brain regions, which helps to explain the multifocal clinical features of this disease, but other antibodies are likely to play a role in some patients and need to be characterized in future studies.